Different Mechanisms of Two Subtypes of Perforating Artery Infarct in the Middle Cerebral Artery Territory: A High-Resolution Magnetic Resonance Imaging Study - Liao, Siyuan; Deng, Zhezhi; Wang, Yuge; Jiang, Ting; Kang, Zhuang; Tan, Sha; Shan, Yilong; Zou, Yan; Lu, Zhengqi (Frontiers in Neurology, 2018)
Abstract Purpose Perforating artery infarcts (PAIs) can be divided into two subtypes based on their etiologies: branch atheromatous disease (BAD) and lacunar infarct (LI). Recent studies have shown that while both subtypes can be caused by large artery lesions, the different mechanisms that underlie their development are not clear. This study was designed to use high-resolution magnetic resonance imaging (HRMRI) to explore the differences in that contribute to the occurrence of these two subtypes in large artery lesions in the anterior circulation. Methods In all, 50 patients with an acute perforating artery infarct in the anterior circulation were enrolled (32 BAD and 18 LI patients). The ipsilateral middle cerebral artery (MCA) was scanned with HRMRI to analyze atherosclerosis plaques. Artery remodeling and plaque characteristics of MCA lesions were compared between the two subtypes. Results The rate of MCA lesions was significantly higher in BAD than in LI (P=0.033). Lumen areas were smaller in BAD than in LI (P<0.001), and plaque area (P=0.001) and plaque burden (P<0.001) were higher in the BAD group. Most BAD patients showed non-positive remodeling, while the great majority of LI patients showed positive remodeling (P<0.001). Conclusion In the anterior circulation, a considerable proportion of both BAD and LI share connections with atherosclerotic plaques in large arteries. BAD patients mainly showed relatively large and stable atherosclerotic plaques in large arteries, while LI patients mainly exhibited relatively small and unstable atherosclerotic plaques in large arteries. Clinical Trial Registration This clinical trial is a retrospective study and therefore does not require registration.